Depositional environment of the Quebradagrande complex : implications for the early to mid-Cretaceous tectono-magmatic evolution of the northern Andes (2018)
The sedimentary and volcano-sedimentary rocks of the Quebradagrande Complex on the northwestern margin of South America record the arc and its associated back-arc tectonic settings. Sixteen thin sections were analyzed revealing distinct lava facies from basic to intermediate compositions. Field relations, six stratigraphic sections and petrographic analysis allow the identification of three main lithofacies: Sedimentary, effusive and pyroclastic. Their spatial relation shows an east to west transition from deep ocean sediments, basic lava compositions and gravity flow pyroclastic deposits to shallower depositional environments, intermediate lava compositions and fall pyroclastic deposits. The results obtained in this study confirm the tectono-magmatic models previously proposed in which a para-autochthonous island arc along with a marginal basin were stablished for early to mid-Cretaceous ages